Management of sexually transmitted diseases at the Jipijapa Type B Health Center, Ecuador - Zambrano, Génesis F.; Villamar, Saimon S.; Rodríguez, Dayana M.; Cárdenas, Michel L.; Burgos, Bayron S.; Talledo, Diego A. (Revista Gregoriana de Ciencias de la Salud, 2025)
Sexually transmitted diseases (STDs) continue to be a major challenge for global health due to their high level of prevalence and complications. This study identified key factors to improve the effectiveness of primary care in detecting and managing STDs. The literature on the prevalence and treatment of STDs in primary care was reviewed using a cross-sectional approach. The importance of early detection and appropriate management was highlighted in order to reduce complications such as infertility and the risk of HIV transmission. The barriers identified include lack of resources, social stigma, and insufficient sexual education, especially in low-income countries. The study concludes with recommendations to improve health personnel training and implement educational programs encouraging patient participation in preventing and treating STDs.